Биосинтез нуклеиновых кислот и белков в клетках хлопчатника на стадии каллусогенеза - Арипджанов, Ш.А.; Хакимов, Х.А.; Ходжаева, Ш.Х. (Биополимеры и клетка, 1989)
В культуре ткани тетраплоидных видов хлопчатника Gossypium hirsutum L. и G. barbadense L., а также их гибридной линии A-4I48 исследована динамика активности синтеза ДНК, РНК и белков в процессе каллусогенеза с помощью ³Н-тимидина, ³Н-уридина и ¹⁴С-лейцина. Обнаружены некоторые особенности включения меченых предшественников в клетки хлопчатника в различные фазы каллусогенеза. У культурі тканини тетраплоідних видів бавовнику Gossypium hirsutum L. і G. barbadense L., а також їх гібридної лінії A-4I48 досліджена динаміка активності синтезу ДНК, РНК і білків в процесі каллусогенеза за допомогою ³Н-тимідину, ³Н-уридину і ¹⁴С-лейцину. Виявлено деякі особливості включення мічених попередників у клітини бавовнику в різні фази каллусогенеза. The biosynthesis activity of nucleic acids (DNA and RNA) and proteins during callu-sogenesis phase in tetraploid cells of G. hirsutum L., G. barbadense L. as well as their hybrid line A-414'8 was studied to research cell metabolism in cotton tissue culture. Nonuniform character of incorporation of labelled predecessors in cells during different periods of callusogenesis is found. The activity of label incorporation in nucleic acids reaches its maximum level in the first 6–8 days, then decreases to definite constant level in the terminal part of callusogenesis phase. Synthesis of proteins in cotton cells during callusogenesis is distinguished by tendency to an increase of its intensity. These peculiarities of nucleic acids and proteins metabolism are characteristic of both parents and of their hybrid line, indicating to a definite bond between genotype of cell and its reaction to transfer from native conditions to artificial ones.